Revealed demand patterns of people with disabilities in on-demand ridepooling - Nico Kuehnel; Felix Zwick; Tom-Erik Kuhlen (European Journal of Transport and Infrastructure Research)
Since 2023, the on-demand ridepooling service MOIA operates, as part of Hamburg's public transport, an integrated wheelchair-accessible service and offers subsidized fares for individuals with severe disabilities. This study analyzes one year of demand patterns in Hamburg following these enhancements, utilizing data analyses to assess their impact on service usage and accessibility. Findings reveal insights into distinct spatio-temporal user behavior, offering valuable guidance for the development of large-scale urban mobility solutions.